THE ROLE OF TECHNOLOGY IN CHANGING MODERN BUSINESS DYNAMICS - Aurelia Widya Astuti; Ratih Muhafifah; Sayudin sayudin (Interdisciplinary Journal of Advanced Research and Innovation, 2023)
In the era of technological revolution, the role of technology is key in changing the modern business paradigm, creating success through innovation. Information technology, artificial intelligence and connectivity accelerate business transformation, enabling operational process optimization and real-time access to data for product and service innovation. Developments like the Internet of Things (IoT) provide deep insights into business performance and customer preferences, while artificial intelligence and big data analysis enable more accurate decisions. Case studies show that technology positively influences operational efficiency, product innovation and customer satisfaction. This research uses qualitative methods. This research collects data about technology's role in changing modern business dynamics through online analysis, literature studies and surveys. The results show that information technology, with its ease of communication, data management efficiency, and CRM convenience, has become the backbone of modern enterprises. Technological innovation and digital transformation are the main drivers of growth and change in business. By understanding technology integration in business networks, this article provides a holistic view of the fundamental changes in modern industry. This invites companies to optimize the role of technology to achieve sustainable growth and resilience in the face of growing economic uncertainty.